USE OF THE GROUNDWATER QUALITY INDEX, MULTIVARIATE STATISTICS AND HYDROGEOCHEMISTRY FOR GROUNDWATER ASSESSMENT IN THE MALABAR VOLCANIC AREA, INDONESIA - Rizka Maria; Anna Fadliah Rusydi; Dyah Marganingrum; Retno Damayanti; Heri Nurohman; Hilda Lestiana; Riostantieka Mayandari Shoedarto; Asep Mulyono; Yudi Rahayudin; Taat Setiawan; Teuku Yan Walliana Muda Iskandarsyah; Bombom Rachmat Suganda; et al. (Rudarsko-geološko-naftni Zbornik)
The South Bandung basin has had significant population growth in the last ten years, particularly in the regions that border West Java. Consequently, there was an increase in the demand for groundwater, an essential resource for numerous uses. On the other hand, human activities have given impact significantly on the change of groundwater quality in the Bandung basin, the Malabar volcanic area. In the Bandung basin, the Malabar volcanic area has become an important location for urban water supply recharge. Within the current investigation 27 water samples were collected during the dry and wet seasons. The purpose of this study was to analyze the seasonal variability of parameters using different approaches. The comprehensive methods involving the application of multivariate statistics, geographical modelling, and the groundwater quality index. The spatiotemporal variability showed that the dilution effect of precipitation during the rainy season contributed to the significant seasonal variations. The hydrogeochemical facies was determined as Ca-Cl, CaMg-Cl, CaMg-HCO₃, and NaK-HCO₃. The Ground Water Quality Index (GWQI) analysis indicated that physicochemical factors influence water quality classifications from unsuitable to excellent. According to the conceptual model, the upstream area has excellent GWQI; however, the downstream area has decreased GWQI due to anthropogenic influence and the dissolution process. The results suggest that NH₄⁺-N, Fe²⁺, and Mn²⁺ have significant impact on GWQI. The novelties of this research include sensitivity analysis of each parameter to GWQI while conceptual model differentiates its findings from previous research. This conceptual model can be applied in various geographic environments to determine groundwater quality and its distribution regarding seasonal and land use changes.